Analisis Percepatan Waktu dengan Menggunakan Metode Crashing (Studi Kasus: Pekerjaan Jembatan Owata pada Proyek Paket III Bendungan Bolango Ulu) - Silva Nurhikma Bonde; Mohamad Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2025)
A project is a series of activities aimed at achieving specific objectives within limited time, resources, and constraints. In complex construction projects, such as dam and bridge construction, proper planning, execution, control, and monitoring are crucial to ensure timely completion. Delays in such projects can lead to increased costs and missed targets. This study focuses on the time acceleration of the Owata Bridge construction, which is part of the Bolango Ulu Dam Package III Project. The method used in this research is the crashing method, a project management technique used to shorten project duration at the lowest possible cost. The analysis was carried out on the foundation and abutment work components of the bridge. Based on the crashing analysis through the addition of workforce on critical path activities, the total project duration was successfully reduced by 17 days or 9.39%, from an initial duration of 181 days to 164 days. However, this acceleration led to an increase in total project cost from Rp. 4,125,666,382.00 to Rp. 4,153,661,940.15, resulting in a cost difference of Rp. 27,995,558.15, or an increase of approximately 0.7%. These findings indicate that time efficiency can be achieved with minimal cost implications using the crashing method. This research contributes to better project planning and decision-making in infrastructure development, especially in projects with tight deadlines and significant social-economic impacts.